Comparative Analysis of Financial Performance PT. Waskita Karya Tbk and PT. Wijaya Karya Tbk with Independent Sample T-Test Method Levene Period 2014 - 2023 - Ramdhani Agung Sukirno; Muhammad Gilang Rahmadani; Donald Bintang Satria (Jurnal Multidisiplin Indonesia, 2025)
The Ministry of SOEs has made the decision to keep running businesses like PT Wijaya Karya Tbk (WIKA) and PT Waskita Karya Tbk (WSKT) despite financial problems and threats of dissolution. The financial condition of the two BUMN Works is currently experiencing a significant decline for almost all performance indicators. From the Financial Statements of the two BUMN works for the last 5 (five) years, several financial ratio indicators show financial performance that leads to Financial Distress conditions. Both BUMN Karya are still maintained because they contribute significantly to the country’s economy and have a sustainable business model. The purpose of this study is to compare The financial outcomes of PT Waskita Karya Tbk and PT Wijaya Karya Tbk. The debt to equity ratio, operating cash flow ratio, interest coverage ratio, current ratio, and return on assets are among the financial performance metrics that are examined. Levene’s Independent Sample T-Test method is the method of data analysis used in this inquiry. The results showed that in most financial ratios, PT Wijaya Karya (Persero) Tbk fared better than PT Waskita Karya (Persero) Tbk.